4
$\begingroup$

I know that problems similar to this one, involving either one of the two bounds, have been posted before, but I would like just a hint in the last part of the proof involving the upper bound, with which I have some troubles with being ''convincing'' enough.

Prove that $2(\sqrt{n+1} - \sqrt{n}) < \frac{1}{\sqrt{n}} < 2(\sqrt{n}-\sqrt{n-1})$ if $n\geq 1$. Then use this to prove that

$$2\sqrt{m}-2 < \sum_{n=1}^m\frac{1}{\sqrt{n}}< 2\sqrt{m}-1 \qquad \text{if }\ m \geq 2$$

With some help I received here I got the following proof for the first set of inequalities:

Proof (direct):

Since

$$\sqrt{n+1} - \sqrt{n} = \frac{1}{\sqrt{n+1} + \sqrt{n}} < \frac{1}{\sqrt{n} + \sqrt{n}} = \frac{1}{2\sqrt{n}}$$

then we have

$$2(\sqrt{n+1} - \sqrt{n}) < \frac{1}{\sqrt{n}}\qquad (1)$$

Likewise, since

$$\frac{1}{2\sqrt{n}} = \frac{1}{\sqrt{n} + \sqrt{n}} < \frac{1}{\sqrt{n} + \sqrt{n-1}} = \sqrt{n} - \sqrt{n-1}$$

then

$$\frac{1}{\sqrt{n}} < 2(\sqrt{n} - \sqrt{n-1})\qquad (2)$$

as asserted.

For the second part I tried to prove the lower bound firt:

Proof (direct): From $(1)$ we have

$$\sqrt{n+1} - \sqrt{n} < \frac{1}{2\sqrt{n}}$$

By summing both sides we get

$$\sum_{n=1}^{m}(\sqrt{n+1} - \sqrt{n}) < \sum_{n=1}^{m}\frac{1}{2\sqrt{n}}$$

And after applying the telescoping property on the LHS, this becomes

$$\sqrt{m+1} - 1 < \sum_{n=1}^{m}\frac{1}{2\sqrt{n}}$$

But since $\sqrt{m} - 1 < \sqrt{m+1} - 1$, by transitivity we have

$$\begin{align*}\sqrt{m} - 1 &< \sum_{n=1}^{m}\frac{1}{2\sqrt{n}}\\ 2\sqrt{m} - 2 &< \sum_{n=1}^{m}\frac{1}{\sqrt{n}}\end{align*}$$

Then the upper bound:

Proof (direct): From $(2)$ we have

$$\frac{1}{2\sqrt{n}}< \sqrt{n} - \sqrt{n-1}$$

By taking the sum of both sides we get

$$\sum_{n=1}^{m}\frac{1}{2\sqrt{n}}< \sum_{n=1}^{m}(\sqrt{n} - \sqrt{n-1})$$

If we apply the telescoping property on the RHS, the inequality becomes

$$\begin{align*}\sum_{n=1}^{m}\frac{1}{2\sqrt{n}} &< \sqrt{n}\\ \sum_{n=1}^{m}\frac{1}{\sqrt{n}} &< 2\sqrt{n}\end{align*}$$

Here I'm not sure how to get the $-1$ on the RHS that I'm lacking. I could have started the summation at $n=2$ I guess, but don't think it's correct and it doesn't seem to be a convincing way to complete the proof.

$\endgroup$
2
$\begingroup$

Well you tagged induction so why not use it:

$$ \sum_{n=1}^{m+1} \frac{1}{\sqrt{n}} \lt 2\sqrt{m}-1 + \frac{1}{\sqrt{m+1}} \lt 2\sqrt{m}-1 + 2(\sqrt{m+1}-\sqrt{m}) = 2\sqrt{m+1}-1 $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ @Jazz yes, actually starting the summation at $n=2$ works like a charm. Why did you think it was incorrect? $\endgroup$ – benji Feb 9 '15 at 21:07
-1
$\begingroup$

For the lower bound, proof (direct): from $(1)$:

$$2(\sqrt{n+1} - \sqrt{n}) < \frac{1}{\sqrt{n}}$$

By summing both sides:

$$2\sum_{n=1}^{m}(\sqrt{n+1} - \sqrt{n}) < \sum_{n=1}^{m}\frac{1}{\sqrt{n}}$$

After applying the telescoping property on the LHS, the inequality becomes

$$2\sqrt{m+1} - 2 < \sum_{n=1}^{m}\frac{1}{\sqrt{n}}$$

For the upper bound, proof (direct): from $(2)$:

$$\frac{1}{\sqrt{n}}< 2(\sqrt{n} - \sqrt{n-1})$$

By taking the sum of both sides from n=2:

$$\sum_{n=2}^{m}\frac{1}{\sqrt{n}}< \sum_{n=2}^{m}2(\sqrt{n} - \sqrt{n-1})$$

Add 1 on both sides:

$$1+\sum_{n=2}^{m}\frac{1}{\sqrt{n}}< 1+2(\sum_{n=2}^{m}(\sqrt{n} - \sqrt{n-1}))$$

$$\sum_{n=1}^{m}\frac{1}{\sqrt{n}}< 1+2(\sum_{n=2}^{m}(\sqrt{n} - \sqrt{n-1}))$$

Apply the telescoping property on the RHS, the inequality becomes

$$\begin{align*}\sum_{n=1}^{m}\frac{1}{\sqrt{n}} &< 1+2(\sqrt{m}-1)\\ \sum_{n=1}^{m}\frac{1}{\sqrt{n}} &< 2\sqrt{m}-1\end{align*}$$

So $$2\sqrt{m+1} - 2 < \sum_{n=1}^{m}\frac{1}{\sqrt{n}} < 2\sqrt{m} - 1$$


This can be relaxed to:

$$2\sqrt{m}-2<2\sqrt{m+1}-2<\sum_{n=1}^{m}\frac{1}{\sqrt{n}}<2\sqrt{m}-1< 2\sqrt{m}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.